Digital dilemma: technology in the vote counting process for general elections and local head elections in Indonesia - Habibi, Muhammad; Mahadika, Alam; Astuti, Widia (Department of Government Studies, Universitas Muhammadiyah Makassar, 2023)
The traditional methods of vote counting and recapitulation, which include manual and layered processes, are important to ensuring data security and addressing a lack of understanding of public information technology. However, it is essential to quickly and properly disseminate election results among an increasing number of survey findings within the community. Despite this contradictory scenario, it is imperative to employ information technology tools like SITUNG and SIREKAP to ensure transparent dissemination of election outcomes. The study applies a descriptive qualitative approach, collecting primary and secondary data sources including official documents, journal articles, and textbooks. By using three analysis techniques; first, by tabulating the data; second, to categorize the data; third, interpreting the findings based on the theoretical and construction of the data. The results of this study showed three main challenges to the use of digital-based recapitulation: first, the lack of a clear legal basis for the SITUNG and SIREKAP applications, which has triggered criticism from election participants and observers; second, incomplete system support characterized by limited network connectivity, which has created difficulties for field operators in the local level; and third, inappropriate data management in the SITUNG and SIREKAP applications, which included incorrect data entry. Election organizers should be aware that technology-based recapitulation data can become digital evidence for contesting parties in election courts.